Libraries, information and coup d’ etats: theory in the context connected to the political crisis in Honduras - Meneses Tello, Felipe (Revista General de Información y Documentación, 2012)
The analysis presented is limited whitin the framework of the connection that exists among “libraries, information and coup d’etats”, therefore it fits as an aspect of analysis and study in the field of what is appropriate to call Political Library Science. The theory is made up by four headings: 1] Gabriel Naudé, political librarian who coined the term coup d’etat, 2] The concept of coup d’etat in relation with the documentary and information world, 3] Libraries and coup d’etats, 4] Information and coup d’etats; the context is shaped by the following two sections: 5]The coup d’etat in Honduras, a danger for its libraries and librarians, and 6] The usurping government in Honduras attacks the freedom of access to information. In this way, the author perceives that coup d’etats show a great variety of facts regarding the period of repression and destruction that bibliographic traditions, libraries and librarians have suffered, among other figures of bibliographic culture.
Keywords: Libraries; Information; Destruction of Libraries; Destruction of Books; Culture Destruction; Coup d’Etat; Censorship; Honduras